The impact of mission valence on innovative work behavior among civil servants: the roles of harmonious passion, spiritual leadership, and the organization’s fault-tolerant climate - Liu, Xi; Zhang, Shaobo; Huang, Qian (Frontiers in Psychology, 2025)
BackgroundCivil servants’ innovative work behavior is crucial for government transformation and the improvement of public service efficiency, especially in developing and transitional countries. However, the pathways to effectively motivate innovative work behavior among civil servants remain to be further explored in academic research.ObjectiveThis study, grounded in the Conservation of Resources Theory and the Broaden-and-Build Theory of Positive Emotions, aims to explore whether and how mission valence affects the innovative work behavior of civil servants in China. Specifically, this research constructs a moderated mediation model to examine the mediating role of harmonious passion, as well as the moderating effects of spiritual leadership and the organization’s fault-tolerant climate.Materials and methodsThis study collected valid matched data from 456 civil servants in China through a two-wave survey. We conducted reliability and validity analysis, correlation analysis, hierarchical regression, and Bootstrapping tests using SPSS 27.0 and AMOS 24.0 to validate the proposed theoretical model.ResultsThe empirical results indicate that: (1) Mission valence has a significant positive effect on civil servants’ innovative work behavior; (2) Harmonious passion partially mediates the relationship between mission valence and innovative work behavior of civil servants; (3) Spiritual leadership positively moderates the relationship between mission valence and harmonious passion of civil servants; (4) Organization’s fault-tolerant climate positively moderates the relationship between harmonious passion and innovative work behavior, and also positively moderates the mediating effect of harmonious passion.ConclusionThis study deepens the understanding of the relationship between mission valence and innovative work behavior of civil servants in the Chinese context. The findings provide practical insights for public sector managers to develop effective strategies, such as strengthening organizational mission promotion, fostering harmonious passion, advocating spiritual leadership, and cultivating a fault-tolerant climate, to enhance civil servants’ innovative work behavior.